2017
DOI: 10.17116/jnevro20171174228-33
|View full text |Cite
|
Sign up to set email alerts
|

Associations between chronotype, road accidents and polymorphisms in genes linked with biological clock and dopaminergic system

Abstract: A mixed chronotype with high levels of morning and evening alertness prevailed in the group. A prominent social jetlag caused by shift work was found. For SNP in PER3 gene there was an association with morning activation. SNP in CLOCK gene was associated with social jetlag and the risk to cause a crash. Minor alleles of SNPs in NPSR1and SLC6A3 correlated with later chronotype and increased risk of a road accident. We suppose that these polymorphisms may be amongst the genetic factors connecting chronotype and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 19 publications
0
2
0
Order By: Relevance
“…Being a T-allele carrier did contribute significantly to the risk of repeatedly committing DWI, showing indeed increased impulsivity and more serious alcohol-related problems among T-allele carriers. Recently in a study of bus drivers, NPSR1 A/A homozygotes had higher incidence of self-reported traffic accidents (44,54). In our study, we did not find any association between NPSR1 and traffic accidents.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Being a T-allele carrier did contribute significantly to the risk of repeatedly committing DWI, showing indeed increased impulsivity and more serious alcohol-related problems among T-allele carriers. Recently in a study of bus drivers, NPSR1 A/A homozygotes had higher incidence of self-reported traffic accidents (44,54). In our study, we did not find any association between NPSR1 and traffic accidents.…”
Section: Discussionmentioning
confidence: 97%
“…NPS has up to 10 times higher potency at the receptor encoded by the T-allele (107Ile) compared to the A-allele-encoded receptor, leading to more effective signal transduction with mobilization of intracellular Ca 2+ , stimulation of cyclic adenosine monophosphate synthesis and induction of mitogen-activated protein kinases phosphorylation (43). Recently Taranov and colleagues (44) found in a study with bus drivers that NPSR1 was associated with increased risk of a road accident. The T-allele of the NPSR1 rs324981 polymorphism has been associated with increased impulsivity and ADHD-related traits (39,42).…”
Section: Introductionmentioning
confidence: 99%